Identifikasi Berbagai Masalah Yuridis dalam Formulasi Perundang-Undangan Pidana - Sri Kartini; Fadjrin Wira Perdana; Irwan Irwan; Doharmam Lumban Tungkup; Miran Miran (CV. Publikasi Indonesia, 2022)
Criminal law contains several regulations containing prohibitions and requirements determined by the state and if these are violated, they are accompanied by criminal threats. Acts against the law in criminal law are regulated in the Criminal Code (KUHP), while criminal laws outside the Criminal Code are referred to as special crimes. However, several policies on the formulation of criminal provisions contain juridical problems. The purpose of this research is to identify various juridical problems in the formulation of criminal legislation. The research method used in this research is descriptive with a qualitative approach. The results of the study indicate that the identification of various juridical problems in the formulation of legislation includes 1) Juridical Formulation Problems in Provisions of 5 Special Laws outside the Criminal Code; 2) The problem of not determining the formulation of the offense as a